Tales of the city [videorecording (DVD)] - Maupin, Armistead; Reid, Alastair, 1939-2011; Linney, Laura; Dukakis, Olympia; Gibson, Thomas, 1962-; Campbell, William, 1959-; Posey, Parker, 1968-; Gross, Paul, 1959- (Acorn Media, 2013)
Freewheeling to San Francisco, Mary Ann Singleton quickly realizes just how far from Cleveland she really is. Moving into a funky house at Twenty-eight Barbary Lane where her landlord welcomes her with a joint, Mary Ann befriends the other residents and finds a good-natured home amid the drugs, drama, and debauchery. Based on Armistead Maupin's beloved novel, the Peabody Award-winning PBS miniseries deftly chronicles the quest for love and connection across a spectrum of sexual experiences.